ASUPAN GIZI DAN FUNGSI KOGNITIF LANSIA WANITA DI POSLANSIA SUBADRA KECAMATAN DRAMAGA KABUPATEN BOGOR - Nunung Cipta Dainy; Rosyanne Kushargina; Fauza Rizqiya (ARGIPA (Arsip Gizi dan Pangan), 2022)
Alzheimer's disease is one of the leading causes of dementia caused by a progressive decline in cognitive function. In Indonesia, the incidence of Alzheimer's disease increases from year to year. Nutritional intake and physical activity are associated with a reduced risk of Alzheimer's disease. The objectives are to describe the intake of macronutrients, micronutrients, and cognitive function of the elderly and to analyze the relationship between intake of macronutrients and micronutrients with cognitive function. The research design used cross-sectional. The subject was 60 older women who met the inclusion criteria. The data collected in primary data include characteristics, intake of macronutrients, and micronutrients (fiber, folic acid, vitamin B12) using 24-hour Food Recall; cognitive function data using the Short Portable Mental Status Questionnaire depression level data using the Geriatric Depression Scale questionnaire. The relationship between nutritional intake and cognitive function was analyzed using the Spearman correlation test. The average intake of macronutrients except for fat and micronutrients of the subjects was in the lower category. There was a significant relationship between fiber and folic acid intake with cognitive function.  As many as 53.33% of the elderly have a normal cognitive function, and the rest (46.67%) have impaired cognitive function, ranging from mild to severe. There is a significant relationship between fiber and folic acid intake with cognitive function. Fiber and folic acid intake must be increased to prevent cognitive decline in the elderly.